Homestay programmes in Malaysia / Dr. Muhammad Hanif Othman - Othman, Muhammad Hanif (Universiti Teknologi MARA, Kedah, 2022)
The Malaysia homestay programme began informally in the 1970s with the involvement of the local community, who provided accommodation, breakfast, and dinner to foreign tourists by charging a minimal price compared to hotels or resorts (Hamzah, 2008; Kayat, 2010; Ibrahim & Razzaq, 2010). At that time, most of the Malays, who live in Malay kampungs (villages) along the beach and in rural areas, provided their houses as homestays for tourists (Ibrahim & Razzaq, 2010). In 1988, with encouragement and support from the Ministry of Tourism, a community of five villages in Pahang—consisting of Desa Murni Sanggang, Desa Murni Ketam, Desa Murni Perangap, Desa Murni Sonsang, and Desa Murni Kerdau—established the Desa Murni Homestay as a model for the new Malaysian Homestay Programme (Kayat & Nor, 2006). These villages are located in the Desa Murni area, which is a 15-minute drive from Temerloh, Pahang (Pusiran & Xiao, 2013). The homestay programme provided cultural, social, environmental, and economic benefits to the local population. Following the programme’s success, the Minister of Tourism launched the Malaysia Homestay Programme on the 3rd of December 1995 at Desa Murni, Temerloh, Pahang. This programme was opened to all rural villages in Malaysia (Malay kampungs, Chinese New Villages, Indian settlements, and Orang Asli villages). However, only Malay kampungs participated in this programme since Malays form the majority of populated rural areas. To regulate the homestay programme, the Ministry of Tourism, Arts and Culture (MOTAC) listed the criteria for the house owner (host) to abide by, such as easy access from the main road; suitable house size and separate room for the guest; high standard of hygiene; and the security and safety of parties involved (MOTAC, 2022a). Homeowners are required to attend a training course conducted by the Institute for Rural Advancement (INFRA) under the Ministry of Rural and Regional Development. This requirement aims to ensure that the homestay programme can be successfully implemented.